On Melancholy Rufus of Ephesus - Pormann, Peter E. (SAPERE, 2008)
Rufus of Ephesus' (fl. ca. AD 100) On Melancholy deals with a medical condition oscillating between madness, depression, and bouts of great creativity. This collection of the Greek, Latin, and Arabic fragments makes this text easily available for the first time.